2017
DOI: 10.1007/s00256-017-2729-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI detection of soleus muscle injuries in professional football players

Abstract: The Munich consensus and BAMIC grading systems are useful tools for defining the patient's prognosis and proper rehabilitation time after injury. The MRI feature that we should carefully look for is the extension of edema, as it seems to significantly affect the RTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The imaging study of sport injury and illness in winter sports is to be developed for effective diagnosis and evaluation, which aims to stay in step with the progress in winter sports field. [ 1 2 3 4 ] This will boost the development of sports promoting health strategy and advance the 2022 Winter Olympic Games.…”
mentioning
confidence: 99%
“…The imaging study of sport injury and illness in winter sports is to be developed for effective diagnosis and evaluation, which aims to stay in step with the progress in winter sports field. [ 1 2 3 4 ] This will boost the development of sports promoting health strategy and advance the 2022 Winter Olympic Games.…”
mentioning
confidence: 99%
“…Consistent with previous studies, we found large variation in the RTP period for injuries at each anatomical location. 42,56,57 The MRI data evaluated in this study represent only some of the many variables that could influence the time to RTP after CMSI.…”
Section: Discussionmentioning
confidence: 99%
“…8,41,43,44,52,54 CMSI with more severe AD have been previously reported to have a worse prognosis for RTP, but these results are difficult to compare with those from the current study due to differences in methods. 42,44 Given our large sample, we could adjust for the potential confounding effects of multiple variables. Previous analyses also used different approaches, such as analysis of variance, 24 or referred to the number of weeks rather than days to RTP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations